PENGARUH STRUKTUR MODAL, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - I Dewa Ayu Prajaniti Arimerta; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2023)
The main goal of the company is to increase the value of the company. High corporate value can increase prosperity for shareholders. High company value will be the main attraction for investors to invest in the company. Firm value is the main focus in making decisions by investors to invest in a company. Apart from capital structure, sales growth and company size are also important concerns for investors. This study aims to determine the capital structure, sales growth and company size, on firm value. This study aims to determine the effect of capital structure, sales growth, and company size on food and beverage sub-sector companies in 2019-2021. The research was conducted using the non-participant observation method, the data used was in the form of secondary data obtained on the Indonesia Stock Exchange (IDX) through the website www.idx.co.id. The samples used in this study were thirteen companies which were determined using a purposive sampling method. The analysis technique used in this research is multiple linear regression. Based on the results of the analysis, the capital structure variable has a negative and significant effect on firm value, the sales growth variable has no effect on firm value and firm size has a negative and significant effect on firm value.